Sense and Sensibility à l’écran : l’adaptation entre explication et consolation - Laurent Mellet (Cahiers Victoriens et Edouardiens)
This article purports to study the evolution of TV and film adaptation forms so as to argue for the possibility of an aesthetic that might be specific to adaptation, between explanation and consolation. To do so, it is based on an analysis of three BBC adaptations of Jane Austen’s novel Sense and Sensibility (1971, 1981 and 2008) and of Emma Thompson’s script and Ang Lee’s film (1995). Starting from the assumption that three of the main logics informing the plot and the narrative of the book (Empiricism, the obsession for explanation and the necessity of consolation) can be found at the heart of the aesthetics of these adaptations, we show that the series and the film may complete or contradict one another, but always with a view to setting up some dynamics that help us avoid the logic of comparison and the issue of fidelity. The article concludes on a conceptualisation of adaptation based on a formal and specifically televisual or cinematic appropriation of the processes of explanation (as opposed to mere illustration) and consolation (as opposed to loss and restitution).